Comparison of cyanobacterial bio-fertilizer with urea on three crops and two soils of Ethiopia - Asmamaw, M.; Wolde, G.; Yohannes, M.; Yigrem, S.; Woldemeskel, Endalkachew (Academic Journals, 2019)
Although chemical fertilizers have long been used to meet the high demand of nitrogen (N), the most common limiting nutrient to plant growth, the frequent use of this fertilizer gradually deteriorates soil fertility in addition to its high cost, lower supply and agronomic use efficiency in Ethiopia. Nevertheless, N-fixing cyanobacterial biofertilizers are eco-friendly, and currently considered important to support the developing organic agriculture. Therefore, this study was conducted to evaluate the potential of cyanobacterial biofertilizer for the growth and yield of three commonly growing crops in Ethiopia: maize, kale, and pepper under Alfisol and Andosol, and to investigate the potential contribution of cyanobacteria biofertilizer in selected soil fertility parameters. Three independent factorial experiments were conducted simultaneously in the greenhouse. Each experiment included a factorial combination of four nitrogen fertilizer sources applied at recommendation rate for each crop (control, urea, dried cyanobacteria, and liquid cyanobacteria,) and two soil types with acidic and alkaline pH (Alfisols and Andosols, respectively) arranged in a complete randomized design (CRD) with three replications. Application of dried and liquid cyanobacterial biofertilizer treatments significantly improves the soil N, soil organic carbon (SOC) and available P, Fe and Zn. Cyanobacteria treatments were also found to reduce or maintain the mean soil pH. Accordingly, maximum values of all the vegetative growth attributes of kale, and maize were obtained from the application of two comparable-fertilizer treatments: air-dried cyanobacteria and urea while for pepper crops only dried cyanobacteria. Concentrations of N, P, Zn, and Fe in leaves of kale, pepper, and maize were also significantly increased by air-dried cyanobacterial biofertilizer. Overall, dried cyanobacteria improved the growth and yield of the three crops, and the fertility of the soils. Therefore, the use of dry cyanobacterial biofertilizer could be recommended as a supplementary N source to inorganic fertilizer for kale, pepper and maize production in both study sites.